Kendala Usaha Mikro Dalam Mengakses Kredit Usaha Rakyat (KUR) - Siti Maryama (Liquidity: Jurnal Riset Akuntansi dan Manajemen, 2015)
There are two objectives in this study: (1) to determine how micro businesses in Ciputat in accessing loan credit program (KUR) for their business development; (2) analyze the factors that can be an obstacle in accessing it. The research data obtained through questionnaires and interviews with micro entrepreneurs (traders) who are in the market Ciputat, South Tangerang Municipality. Research analysis techniques using descriptive analysis techniques and quantitative analysis. The variables in the study include independent variables/internal factors and external the dependent variables/constraints. Relationships between variables were examined by using test correlation coefficient. The study concluded that essentially the factors or constraints that may affect businesses in accessing credit consists of internal and external factors. Internal factors consist of background education, their understanding about credit, collateral owned, and the courage to apply for credit. While external factors consist of socialization of KUR, lending, collateral requirements, licensing, and credit application process. This is shown by the average of respondents agree that these factors affect or be an obstacle in accessing credit.